2020
DOI: 10.1111/jdv.16275
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and interobserver concordance: teledermoscopy of 600 suspicious skin lesions in Southern Denmark

Abstract: BackgroundSkin cancer incidences are increasing and early diagnosis, especially of malignant melanoma, is crucial. Teledermatology including teledermoscopy (TDS) can be used to triage referrals of suspicious skin lesions, however, this is not currently recommended in Denmark.ObjectivesTo evaluate diagnostic accuracy, sensitivity, specificity and interobserver concordance of TDS, and to evaluate the number of incidental lesions potentially missed by TDS.MethodsFifty general practices were invited to send images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 26 publications
0
60
1
1
Order By: Relevance
“…As very high sensitivity and specificity rates of the TDS system have already been published, our study did not include an FTF control. In fact, no significant difference in sensitivity was observed between FTF consultations and TDS referrals, especially concerning distinguishing benign versus malignant: diagnostic accuracy for primary diagnosis and benign versus malignant triage with TDS were 58.2% (95% CI 52.3-63.9) and 80.1% (95% CI 75.0-84.5), respectively [9]. In detail, this situation reflects better the final aims of TDS in real-life healthcare conditions: downsizing unnecessary FTF visits and accelerating management of suspicious lesions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As very high sensitivity and specificity rates of the TDS system have already been published, our study did not include an FTF control. In fact, no significant difference in sensitivity was observed between FTF consultations and TDS referrals, especially concerning distinguishing benign versus malignant: diagnostic accuracy for primary diagnosis and benign versus malignant triage with TDS were 58.2% (95% CI 52.3-63.9) and 80.1% (95% CI 75.0-84.5), respectively [9]. In detail, this situation reflects better the final aims of TDS in real-life healthcare conditions: downsizing unnecessary FTF visits and accelerating management of suspicious lesions.…”
Section: Discussionmentioning
confidence: 88%
“…This is less operator dependent compared with teledermatology, as acquisition of images is standardized and highly reproducible [8]. The sensitivity and specificity of TDS have been established previously [9].…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy of results is an unlikely cause for this discrepancy. Recent reviews have shown exceptional diagnostic concordance with store-and-forward teledermatology [38,39]. A review published in 2019 by Andrees et al showed that live-interactive teledermatology was similarly time effective and accurate [40].…”
Section: Discussionmentioning
confidence: 99%
“…found that teledermatology has the potential to diagnose suspicious skin lesions faster, limit the number of direct consultations, triage patients directly for surgical procedures, and provide meaningful feedback to the general practitioners but they also observed that the diagnostic accuracy of teledermatology was significantly lower than that of a face-to-face consultations in identifying benign and malignant conditions. [ 25 ]…”
Section: Dermatologist and Telemedicine In India: Need For Improvemenmentioning
confidence: 99%